2016
DOI: 10.1016/j.jplph.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ROS-scavenging enzymes contribute to acclimation to UV-B exposure in transplastomic tobacco plants, reducing the role of plastid peroxidases

Abstract: Please cite this article as: Czégény Gyula, Martret Bénédicte Le, Pávkovics Dóra, Dix Philip J, HidegÉva.Elevated ROS-scavenging enzymes contribute to acclimation to UV-B exposure in transplastomic tobacco plants, reducing the role of plastid peroxidases.Journal of Plant Physiology http://dx.doi.org/10. 1016/j.jplph.2016.05.026 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
2
9
1
Order By: Relevance
“…The antioxidant marker gene GPX is upregulated under abiotic stress and is thought to be involved in ROS scavenging in Panax ginseng 63 . GSR activity was induced by oxidative stress caused by UV-B radiation in transgenic tobacco plants, thereby giving the plants increased resistance to UV-B stress 64 66 . The increased expression of unigenes encoding GPX and GSR indicates that ROS or other free radicals might be generated in G .…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant marker gene GPX is upregulated under abiotic stress and is thought to be involved in ROS scavenging in Panax ginseng 63 . GSR activity was induced by oxidative stress caused by UV-B radiation in transgenic tobacco plants, thereby giving the plants increased resistance to UV-B stress 64 66 . The increased expression of unigenes encoding GPX and GSR indicates that ROS or other free radicals might be generated in G .…”
Section: Discussionmentioning
confidence: 99%
“…Such mobility facilitates the molecule's messenger function but also requires the antioxidant control of local concentrations further away from H 2 O 2 production sites. Ultraviolet-exposed plants especially need to maintain an effective H 2 O 2 regulating system [17][18][19][20][21][22] since the UV-B (280-315 nm) component of sunlight not only elevates H 2 O 2 concentrations in planta but may also photoconvert H 2 O 2 to more hazardous hydroxyl radicals ( • OH) 8 . Earlier studies have shown that the proper activation of class-III plant peroxidase (POD) enzymes is a key factor in the successful acclimation to UV-B both in model plants exposed to supplemental UV radiation in growth chambers 20 and in sun leaves outdoors 23 .…”
Section: Y(no)mentioning
confidence: 99%
“…The quenching capacity of carotenoids towards different ROS has been widely described (Fiedor & Burda, 2014), as well as their modulation under UV-B radiation (Liu et al, 2011;Castagna et al, 2013). Since UV-B radiation is a potential source of oxidative stress (Czégény, Le Martret, Pávkovics, Dix, & Hideg, 2016), it might be possible that carotenoids were consumed to counteract the potentially damaging ROS. This possibility is in line with the results observed for the phenolic compounds.…”
Section: Terpenoidsmentioning
confidence: 99%